Determining the acceptability of point-of-care urine tenofovir testing and its performance in predicting HIV RNA suppression. (July 2022) - Marryshow, Terry A; Muhairwe, Josephine; Tang, Alice; Molulela, Maleliha Morake M; Matta, Riya; Jordan, Michael R
Background: The detection of tenofovir (TFV) metabolites by point-of-care (POC) urine lateral flow immunoassays (LFIA) indicates adherence to tenofovir-containing HIV pre-exposure prophylaxis. However, the association between urine TFV metabolites as detected by LFIA and HIV viral load suppression in people receiving TFV-based antiretroviral therapy (ART) is unknown as is patient and clinician acceptability of POC urine LFIA testing in clinical practice in low- and middle-income country settings. Methods: We enrolled 409 people living with HIV from two HIV clinics in Lesotho and investigated the performance of POC urine LFIA TFV testing in predicting viral suppression. We interviewed 12 study participants and conducted a focus-group discussion with 5 clinicians to gather opinions on POC urine TFV testing. Results: Using a viral load threshold of 1000 copies/mL, 398 (98%) participants were virologically suppressed, and 8 were viremic. Tenofovir was detected in the urine of 405 (99%) participants. The sensitivity of the POC urine LFIA test in detecting TFV in participants with viral suppression was 99.3% (95% CI: 97.8–99.8); the specificity was 12.5% (95% CI: 0.3–52.6). The positive and negative predictive values were 98.3% and 25%, respectively. Point-of-care urine TFV testing was viewed favorably by both participants and clinicians. However, clinicians stated that the 2–3-days detection window of the assay studied limits adherence categorization. Conclusions: In our study cohort, urine POC TFV testing demonstrated high sensitivity in predicting viral suppression, but low specificity and negative predictive value. Urine POC TFV testing was highly acceptable to participants and clinicians; however, clinicians expressed concern about its clinical utility because of its limitations. While further research is needed to assess performance in less adherent populations, this test may support adherence counseling in some clinical settings.